Regularization by erasement - Martínez-Legaz, Juan-Enrique; Penot, Jean-Paul (Mathematica Scandinavica, 2006)
We study an approximation method for sets and functions which erases corners but keeps smooth parts. Basic properties of such a method are pointed out in a general and simple way. Several convergence results are provided, essentially in the framework of variational analysis.